INTERNATIONAL COMPETITIVENESS OF INDONESIA’S HIGHER EDUCATION SERVICES TRADE - Suryawati, Suryawati; Lizhen, Chen (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2019)
Asia is one of the fastest growing destinations for international students. Therefore, this paper was conducted by conducting a comparative study and empirical study with the aim to find out Indonesia's international competitiveness for the higher education service trade aspect, which is compared with seven other countries. To measure the international competitiveness in the higher education services trade, data from 2010 to 2017 on the number of sending and receiving students in a country and other more complex data have been used to obtain valid results. A comparative study conducted by calculating data from eight countries using the IMS, TCI and RCA measurement methods, and empirical analysis conducted using a questionnaire survey with 302 respondents' data obtained to find out the significant factors that influence the competitiveness. The results show that although Indonesia's higher education service trade is unstable every year, it still has certain competitiveness in the international scope. In addition, culture, quality of higher education and cost of living have a significant impact on the international competitiveness of higher education service trade. On this basis, this paper puts forward some countermeasures and suggestions on how to improve the international competitiveness of Indonesia's higher education service trade, including: promoting the development of Indonesian culture, improving the quality of higher education, reducing tuition fees and living costs, increasing the employment opportunities for foreign students and promoting the balanced growth of Indonesian economy. Keywords: International Competitiveness; Service Trade; Higher Education; Indonesia;